Consumption values, attitudes and continuance intention to adopt ChatGPT-driven e-Commerce AI Chatbot (LazzieChat) - Yao Yue; Siew Imm Ng; Norazlyn Kamal Basha (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2024)
The rapid rise of chat generative pre-trained transformer (Chat GPT) has brought huge opportunities for e-commerce platforms to use it for consumer communication and service. This paper proposes a research framework to expand the value-attitude-behavior model by integrating the theory of consumption values. The purpose is to explore key consumption values that affect consumers' attitudes and their continuance intention to adopt ChatGPT- driven chatbots (i.e., LazzieChat) in the e-commerce services context while examining the moderating effect of online shopping self-efficacy in this process. A questionnaire survey was conducted in Singapore, involving 305 participants who had experienced LazzieChat in Lazada. Use the structural equation modelling of Smarts 4 to analyze the data. The results show that consumer 'attitudes towards LazzieChat have significantly affected their continuance intention to adopt LazzieChat, and online shopping self-efficacy has moderated this relationship. In addition, the research confirms that emotional value and epistemic value are the main driving factors of consumer 'attitudes, followed by functional value, social value and epistemic value. Consumers' attitudes towards LazzieChat mediate the relationship between functional value, social value, epistemic value, and continuance intention to adopt LazzieChat. By developing a research framework that follows the logic of value-attitude-behavior model, this study provides theoretical and practical insights based on the theory of consumer values, which could guide e-commerce platforms to more effectively cater to their consumers' continuance intention of adopting ChatGPT-driven e- commerce AI chatbot service.
Keywords: 330; Theory of consumption value; the value-attitude-behavior (VAB) model; ChatGPT; chatbots; LazzieChat continuance intention; inline shopping self-efficacy